(untitled) (Czech Journal of International Relations, 2010)
The paper seeks to find the relationship between the philosophical debate on absolute and relative space and the IR debate on territoriality. It shows the relation between the absolute space concept and the territorial definition of the modern state. It also seeks to find parallels between relativity and relative space on one hand and the current questioning of territoriality and attempts to find a substitute for it on the other. Due to the fact that relativity has not been overthrown in philosophy of physics, the article concludes that we cannot expect a relative conception of space to disappear from IR either.